PTU-133 Predictors of peritoneal metastasis in gastric cancer. (22nd June 2015) - Harris, C; Ostwal, V; Goel, M; Bal, M; Shrikhande, S
Abstract : Introduction: Presence of peritoneal metastasis implies a grave prognosis in gastric cancer. However, imaging modalities fail to detect peritoneal deposits, often leading to surprises at laparotomy. Staging laparoscopy helps to detect these lesions and thereby decide the intent of therapy in locally advanced gastric cancer. But it is invasive and expensive. The purpose of this study is to identify patients in whom this procedure may be avoided. Method: A retrospective analysis of the prospectively maintained database of patients treated for gastric cancers at a tertiary referral centre from 2009 to 2015 was performed. Patients without apparent metastatic disease on imaging, who were subjected to laparoscopy to look for peritoneal metastasis, were analysed. Results: A total of 247 patients underwent staging laparoscopy during the study period. Presence of signet ring cells and mucin in the gastric biopsy, age, gender, site of lesion in the stomach, and levels of Haemoglobin, Albumin, Carbohydrate Antigen 19–9 (CA 19–9) and Carcinoembryonic Antigen (CEA) were studied for their roles in predicting peritoneal metastasis using the Chi-square test. Multivariate logistic regression analysis showed that Signet cell histology (95% CI 0.202–0.955, p = 0.038), CA 19–9 >37 U/mL (95% CI 0.133–0.688, p = 0.004), CEA >5 ng/mL (95% CI 0.167–0.944, p = 0.037), Albumin <3.5 g/dL (95% CI 0.114–0.917, p = 0.032) and lesions involving the entire stomach (95% CI 0.033–0.94, p = 0.042) were independent predictors of peritoneal metastasis. Conclusion: Laparoscopy is essential for staging locally advanced gastric cancers. However, in settings with resource constraints, these predictive factors may help in selecting patients for judicious use of resources. Disclosure of interest: None Declared.